1982
DOI: 10.1002/ajh.2830130108
|View full text |Cite
|
Sign up to set email alerts
|

Results of induction therapy with vincristine and prednisone alone in adult acute lymphoblastic leukemia: Report of 43 patients and review of the literature

Abstract: The complete remission (CR) rate in children with acute lymphoblastic leukemia (ALL) who received vincristine (VCR) plus prednisone (PRED) alone for induction is > 90%, and has not improved with the use of more intensive regimens. In adults with ALL, using the same regimen, a CR rate of only 50% is frequently quoted, and is apparently based mainly on unpublished data on only 13 patients from an early Acute Leukemia Group B protocol. We reviewed the case records of 43 adults with previously untreated ALL seen b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…In 1976, Cancer Journal published an article reporting complete remission achievement by the use of vincristine and prednisone in most of studied adult patients 20 . A 61 % rate of complete remission in adults has also been shown by Takahashi study 21 and was confirmed by a rate of 66% reported by another study published in the same year 19 . According to these findings and presumptions, here, in Hematology-Oncology and Stem Cell Transplantation Research Center, Sharitai Hospital, eligible patients were offered to undergo HSCT with an induction regimen consisting of dexamethasone and vincristine and the outcomes were retrospectively compared with the outcomes of HSCT following standard induction therapy.…”
Section: Introductionsupporting
confidence: 74%
See 3 more Smart Citations
“…In 1976, Cancer Journal published an article reporting complete remission achievement by the use of vincristine and prednisone in most of studied adult patients 20 . A 61 % rate of complete remission in adults has also been shown by Takahashi study 21 and was confirmed by a rate of 66% reported by another study published in the same year 19 . According to these findings and presumptions, here, in Hematology-Oncology and Stem Cell Transplantation Research Center, Sharitai Hospital, eligible patients were offered to undergo HSCT with an induction regimen consisting of dexamethasone and vincristine and the outcomes were retrospectively compared with the outcomes of HSCT following standard induction therapy.…”
Section: Introductionsupporting
confidence: 74%
“…Later studies revealed lower CR rate as 61% (11 from 18 patients) 21 . Sixty-six percent of adults (total n=43) obtained complete remission in the study of Hess and Zirkle 19 .The CR rate was age dependent in their study. Comparing to our case-control study, all of 49 patients of our cyto-reduction group which received dexamethasone and vincristine for induction therapy achieved complete remission.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…17 Attempts to identify optimal therapy in this population have included adaptations of palliative regimens including vincristine and corticosteroids, and POMP (6-mercaptopurine, vincristine, methotrexate, and prednisone). [43][44][45][46] Although these regimens are unlikely to generate cure, they can palliate the disease and extend survival, with clinical outcomes similar to those achieved with more intensive protocols. It is important to note that older adults with ALL and multiple comorbidities have not typically qualified for clinical trials.…”
Section: Low-intensity Regimensmentioning
confidence: 99%